2021
DOI: 10.1186/s13054-020-03436-x
|View full text |Cite
|
Sign up to set email alerts
|

The immune modulatory effects of mitochondrial transplantation on cecal slurry model in rat

Abstract: Background Sepsis has a high mortality rate, but no specific drug has been proven effective, prompting the development of new drugs. Immunologically, sepsis can involve hyperinflammation, immune paralysis, or both, which might pose challenges during drug development. Recently, mitochondrial transplantation has emerged as a treatment modality for various diseases involving mitochondrial dysfunction, but it has never been tested for sepsis. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Using a rat cecal slurry model, Hwang et al . ( 30 ) have reported that transplantation of mitochondria isolated from rat L6 cells can improve survival rate, mitigate mitochondrial dysfunction, and attenuate hyperinflammation. Our study also demonstrated that intravenous administration of mitochondria isolated from human UC-MSCs (PN-101) and those from human platelets could improve survival rates of LPS-challenged mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using a rat cecal slurry model, Hwang et al . ( 30 ) have reported that transplantation of mitochondria isolated from rat L6 cells can improve survival rate, mitigate mitochondrial dysfunction, and attenuate hyperinflammation. Our study also demonstrated that intravenous administration of mitochondria isolated from human UC-MSCs (PN-101) and those from human platelets could improve survival rates of LPS-challenged mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We used a body weight-adjusted polymicrobial IAI sepsis model according to our previous study [ 15 , 16 ]. In brief, donor rats were anesthetized with an intramuscular injection of Zoletil (50 mg/kg) and xylazine (10 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Once the mitochondria to be transplanted are obtained, they can be incorporated into the tissues with experimental techniques that depend on the site and the type of injury. In in vivo studies, mitochondria have been transplanted through different routes; for example, during administration in the blood circulation (systemic transplantation), mitochondria have been injected through coronary arteries, renal arteries, and the tail vein [109,110,126,127]. Mitochondria have also been transplanted directly to the tissue (in situ transplantation) in the renal capsule, or directly into the myocardium [45,87,89,100,111].…”
Section: Mitochondrial Isolationmentioning
confidence: 99%